THE PLACE OF RELIGION IN THE PSYCHOTHERAPY OF MUSLIM IMMIGRANTS: THE CASE OF FIRST-GENERATION AFGHAN IMMIGRANTS IN CANADA - Tasmim, Samoon (Université d'Ottawa | University of Ottawa, 2024)
This thesis investigates the place of religion and spirituality in the mental health of Muslim immigrants, focusing specifically on Afghan immigrants residing in Canada. The research explores how pre-migration, migration, and post-migration factors impact the psychological well-being of Afghan immigrants and delves into the role of Islam as both a socio-political identity and a religious practice in therapy. Employing a qualitative research approach, grounded theory methodology is utilized to gain a comprehensive understanding of the experiences of Afghan immigrants. Data is collected through constructivist interviews, and an analytic procedure involving initial coding, focused coding, and theoretical sampling is implemented. The findings underscore the multifaceted nature of religion and spirituality in the lives of Afghan immigrants. The research analyzes perspectives from both clients and clinicians regarding the role of religion and spirituality in the therapeutic process. An emergent model is developed, illustrating the interplay of religion and spirituality within the psychotherapeutic journey from multiple vantage points: the therapist outside the therapy room, the therapist and client in the therapy room, and the client outside the therapy room. The findings offer insights into the experiences of Muslim immigrants in Canada, and implications are outlined for clinicians and researchers, emphasizing the significance of incorporating religious and spiritual dimensions in the psychotherapeutic process and promoting culturally responsive mental health care.
Keywords: Religion, Spirituality, Mental health, Muslim immigrants, Afghan immigrants, Spiritually integrated therapy, Cultural responsiveness